Potential of Indigenous Methanotrophic Bacteria as a Biological Control Agent Against Xanthomonas oryzaepv. oryzae Causing Diseases on Rice - Nontji, Maimuna; Amran, Farizah Dhaifina (Makara Journal of Science, 2019)
Methanotrophic bacteria inhabit the rhizosphere and potentially inhibit the growth of pathogens. Therefore, they have potential utility as biological control agents. This study aimed to analyze 10 isolates of indigenous Methanotrophic bac-teria with the potential to act as biological control agents for Xanthomonas oryzae pv. oryzae. Analysis of antagonistic activity was conducted by the direct inhibition method on media using the following parameters: the time to formation of a clear zone, the diameter of the clear zone, and the index of inhibition. The study recommended two isolates as bio-logical control agents that can be combined to inhibit the growth of Xanthomonas oryzae pv. oryzae.